2007
DOI: 10.1007/s10802-007-9181-9
|View full text |Cite
|
Sign up to set email alerts
|

Disaggregating the Distal, Proximal, and Time-Varying Effects of Parent Alcoholism on Children’s Internalizing Symptoms

Abstract: We tested whether children show greater internalizing symptoms when their parents are actively abusing alcohol. In an integrative data analysis, we combined observations over ages 2 through 17 from two longitudinal studies of children of alcoholic parents and matched controls recruited from the community. Using a mixed modeling approach, we tested whether children showed elevated mother- and child-reported internalizing symptoms (a) at the same time that parents showed alcohol-related consequences (time-varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
64
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 43 publications
5
64
3
1
Order By: Relevance
“…Second, our family-informative sample mapping onto the population of children of alcoholic parent(s) who lived in largely lower middle to lower class communities allowed us to contribute to the literature of children of alcoholics. In fact, previous fi ndings from our study have been shown to be consistent with the results of at least two other longitudinal studies on community samples of children of alcoholics (Hussong et al, 2007(Hussong et al, , 2008a(Hussong et al, , 2008b(Hussong et al, , 2008c(Hussong et al, , 2010. Third, our analysis involving female-male sibling pairs made it possible to examine gender differences developmentally while controlling for important confounds such as family density of alcoholism, demographic background, and unequal sample sizes of the gender groups.…”
Section: Discussionsupporting
confidence: 86%
“…Second, our family-informative sample mapping onto the population of children of alcoholic parent(s) who lived in largely lower middle to lower class communities allowed us to contribute to the literature of children of alcoholics. In fact, previous fi ndings from our study have been shown to be consistent with the results of at least two other longitudinal studies on community samples of children of alcoholics (Hussong et al, 2007(Hussong et al, , 2008a(Hussong et al, , 2008b(Hussong et al, , 2008c(Hussong et al, , 2010. Third, our analysis involving female-male sibling pairs made it possible to examine gender differences developmentally while controlling for important confounds such as family density of alcoholism, demographic background, and unequal sample sizes of the gender groups.…”
Section: Discussionsupporting
confidence: 86%
“…The results from these studies indicate a greater risk of internalizing symptoms among children of alcoholics across the developmental period from toddlers (Edwards et al, 2001), preschoolers, and early-school-age children (Puttler et al, 1998) to adolescents (Chassin et al, 1999;Hussong et al, 2008). Parental depression and antisocial behavior, often comorbid with alcohol problems, are known to increase risk of children's internalizing behavior problems, either via increased genetic vulnerability or because of greater exposure to a negative caregiving environment.…”
mentioning
confidence: 99%
“…Alcohol Drugs 70: [741][742][743][744][745][746][747][748][749][750]2009) T HEORIES OF THE EMERGENCE of alcohol problems indicate that alcohol abuse may be a coping mechanism for negative affect such as depression and anxiety (Colder and Chassin, 1997;Swendsen et al, 2000). Children of alcoholics are thought to be at increased risk for such internalizing problems (Hussong et al, 2008;Puttler et al, 1998), although this risk is generally lower than that for externalizing problems (Puttler et al, 1998). However, little is known about the processes involved in the association between parents' alcohol problems and children's internalizing symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These models are frequently used in organizational and educational research to investigate whether relations at Level 1 (e.g., students, employees) vary across Level 2 units (e.g., classes, working teams), or in longitudinal research to assess different developmental trajectories across subjects. For example, Hochweber, Hosenfeld, and Klieme (2014) investigated the relationship between students' mathematics achievement and their math grades, and Hussong et al (2008) examined the effects of parents' alcohol abuse on the development of children's internalizing behavior.…”
mentioning
confidence: 99%